Sekolah Nukleus - implementation of HOTs in the language classroom - Woo, Shiow Ling; Jamaluddin, Noreha; Lee, Siew Ling; Ismail, Lilliati (Institut Pendidikan Guru Kampus Ilmu Khas, Kuala Lumpur, 2017)
In line with Institut Pendidikan Guru Kampus Ilmu Khas‟ (IPGKIK) designation as Pusat Kecemerlangan Kemahiran Berfikir, a series of Cetusan KBAT 2 workshops on Higher Order Thinking Skills (HOTs) was conducted in a primary school in Kuala Lumpur for the English language teachers who were also participants of this research. As a sequel, three more sessions of training were carried out to provide further guidance and support to the teachers. This study investigated the implementation of HOTs in the language classroom. It also examined the teachers‟ confidence in implementing HOTs in the language classroom. Employing a qualitative method approach, data was collected using a semi-structured interview, video recording and an observation checklist. In the interview, the participants claimed that they know how to implement Higher Order Thinking Skills (HOTs) through questioning technique. However, during the observation, the use of Lower Order Thinking Skills (LOTs) questions dominated the lesson. The study also revealed that participants had the tendency to use i-THINK maps in their lessons but lacked conceptual understanding of the correct usage of the maps. The findings further indicated that the participants had differing levels of confidence in implementing HOTs in their lessons. Knowledge of HOTs seemed to be the factor that influenced these levels of confidence. The results would imply the need to further train teachers in incorporating HOTs in class.